2020
DOI: 10.1097/phm.0000000000001408
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Led Photobiomodulation Therapy on Treatment With Knee Osteoarthritis

Abstract: Objective The present study aimed to evaluate the effectiveness of photobiomodulation therapy by light-emitting diode on osteoarthritis treatment in the knees of rats. Design Twenty male Wistar rats were randomly assigned into two experimental groups: OAC: animals subjected to induction of osteoarthritis, without therapeutic intervention and the group OAL: animals subjected to induction of osteoarthritis treated with light-emitting diode photobiomodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…1 . From the initial 1049 records, identified 33 studies (3 in vitro 18 -20 and 30 in vivo 7 -9,21 -47 ) met the eligibility criteria and were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 . From the initial 1049 records, identified 33 studies (3 in vitro 18 -20 and 30 in vivo 7 -9,21 -47 ) met the eligibility criteria and were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The ECM synthesis and/or degradation after LT varied across the included studies. The expressions of COL II (measured by immunoexpression, 21 Western blot, 22 picrosirius red staining, 31,36 and PCR 34,43 ), GAGs (measured by toluidine blue staining 7 ), and ACAN (measured by PCR 34 ) increased significantly following LT. However, there was one study that revealed no effect on COL II and ACAN expressions (measured by immunoexpression 32 and PCR, 43 respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar dos resultados promissores e avanços em experimentos que utilizam técnicas de engenharia de tecidos para reparo da cartilagem, sua tradução para a prática clínica permanece um desafio (Xiang et al, 2020) Dentre estes, vêm se destacando mais recentemente a PBMT por laser de baixa intensidade, uma abordagem terapêutica não invasiva e eficiente para o tratamento clínico de diversas lesões musculoesqueléticas (Bjordal et al, 2010;Hegedus et al, 2009). Sabe-se que esta terapia de luz monocromática, interage com fotorreceptores celulares (cromóforos) específicos e estimulam as propriedades bioquímicas das células, dentre as quais, podemos destacar o aumento da respiração celular e oxigenação tecidual, aumento da síntese de DNA, RNA e proteínas reguladoras do ciclo celular, que podem promover a proliferação celular (Hamblin et al, 2013;Trevisan et al, 2020).…”
Section: Referencial Teórico Osteoartrite De Joelhounclassified